Behavioral response for condom use messages to prevent human immunodeficiency virus/acquired immune deficiency syndrome among Bahir Dar City High School students, North West Ethiopia, 2022: Application of the extended parallel process model - Gebeyehu Lakew; Tadele Fentabil Anagaw; Eneyew Talie Fenta; Eyob Ketema Bogale (SAGE Open Medicine, 2023)
Objective: The human immunodeficiency virus has become one of the world’s most serious health and development challenges. Human immunodeficiency virus prevention has not received sufficient attention, and the prevalence of human behavioral virus infections among Ethiopian high school and preparatory students has also increased. The aim of this study was to assess behavioral responses to condom use messages to prevent human immune virus/acquired immune deficiency syndrome among Bahir Dar city high school and preparatory students using the extended parallel process model, Bahir Dar, Ethiopia, 2022. Methodology: This institution-based cross-sectional study was conducted from 15 November to 15 December 2022, in Bahir Dar city. The data were collected from 601 participants. A multi-stage sampling technique was used to select the study participants. Data were entered into Epi-Info version 7.2.5 and exported to SPSS version 26 for analysis. Descriptive statistics, percentages, and frequencies were calculated. Bivariable logistic regression was performed to identify variables candidates for multivariable logistic regression at p -values less than 0.25, and multivariable logistic regression was performed to identify factors associated with the outcome variable at p- values < 0.05. A 95% confidence interval and odds ratio were used for the interpretation of the association. Result: The response rate of the respondents was 94.9%. The behavioral response for condom use messages was affected by grade level adjusted odds ratio, 0.473, 95% CI (0.252–0.886), knowledge adjusted odds ratio, 2.627, 95% CI (1.788–3.859), attitude adjusted odds ratio, 3.19, 95% CI (2.145–4.744), efficacy adjusted odds ratio, 3.286, 95% CI (2.03–5.339), and threat adjusted odds ratio, 0.249, 95% CI (0.167–0.369). The behavioral response for condom use messages was associated with danger control. Conclusion: The danger control response is 60.9%. Grade level, knowledge, attitude, and perceived and threat efficacies were independent predictors of danger control. Therefore, messages must aim to enhance threat component perception with appropriate efficacy to control danger and developed using scientific health communication strategies to promote behavioral change.